Pengembangan Aplikasi Inovatif dengan Transparansi Informasi untuk Jual Beli Mobil Bekas Menggunakan Design Thinking - Sabil, Al Qamah; Wahyurini, Octaviyanti Dwi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Nowadays, the used car buying and selling industry faces serious challenges in terms of information transparency which can hamper the transaction process and reduce the level of trust between sellers and buyers. In an effort to overcome this problem, this research proposes an innovative solution by applying the principles of Design Thinking. Design Thinking principles involve deep understanding of users, collaboration with stakeholders, and repeated iterations in application design and development. This research began by analyzing existing used car buying and selling applications and identifying the main problems faced by users. At this stage, most of the existing applications were found to be unable to provide adequate information about the condition of used cars, maintenance history and transparent prices. The result of this development is an application that allows users to easily search for used cars, get complete and accurate information about the condition of the car, and determine a fair price based on transparent market data. The results of this research include designing a used car buying and selling application that is more user friendly, integrating important features such as verifying car condition, maintenance history, ownership and legality of documents